Seed weight and germination behavior of the submerged plant Potamogeton pectinatus in the arid zone of northwest China. Issue 7 (6th March 2015) - Li, Zhongqiang; Lu, Wei; Yang, Lei; Kong, Xianghong; Deng, Xuwei
Abstract Variation in seed weight is common within and among plant species, but few studies have attempted to document the pattern of seed weight and germination attributes for aquatic macrophytes at a large scale. This study examined within‐species variation in seed weight and germination attributes and the effects of environmental factors on seed traits of the submerged plant Potamogeton pectinatus in the arid zone of northwest China. Our results showed that the average seed weight was 0.24 g per 100 seeds with a coefficient of variation (CV) of 28.4% among the eight P. pectinatus populations. The total germination fraction of seeds of P. pectinatus was relatively poor, less than 35% in seven P. pectinatus populations, and the lowest germination percentage found was only 2%. There were significant differences in seed weight, time to onset of germination, and total germination fraction among the eight different populations. Hierarchical partitioning analysis showed a strongly positive correlation between seed weight and water temperature and pH. Seed weight and the maternal environmental factors significantly affected both time to initiation of germination and total germination fraction. Our results suggest that (1) seed weight variation in P. pectinatus primarily is the result of temperature variation during fruit development; (2) relatively poor germination fraction suggests that seeds are relatively unimportant in the short‐term survival of populations and that it may be another adaptive trait allowing plants to take place in the right place and at the right time, especially in harsh environment; and (3) variation in seed germination traits should be determined by local environmental and intrinsic factors that interact in a complex fashion.